ANALISIS KESEJAHTERAAN MASYARAKAT SETELAH BERAKHIRNYA COVID-19 PADA RT 002 DAN 015 KELURAHAN KASANG JAYA KECAMATAN JAMBI TIMUR - Dina Linawati; Redi Indra Yudha (Universitas Batanghari Jambi, 2023)
This study aims to find out how is the welfare of the community and what are the activities to improve community welfare after the Covid-19 pandemic in Kasang Jaya Village, East Jambi District. The type of research used is qualitative research with a case study approach. Case study instruments in qualitative research researchers must be able to complete the data and compare it with the facts in the field. Basically, cases are chosen because they are thought to contain their own specialties. While generalization is to show the position of the important things from the case in the knowledge map that has been built. The results showed that (1) The community must be able to adapt to all conditions, especially if there is an urgent situation for the community such as the Covid-19 pandemic which requires the community to be able to adapt to the changes that occur, where this has an impact on several things such as declining people's income, loss of jobs, and changes in people's lifestyles that have become their daily habits, and (2) Each community has a different way they choose, so that they are able to meet their needs and other needs when a condition such as the co-19 pandemic occurs, such as prioritizing important things first and looking for new business opportunities to increase income. Keywords : Public Welfare, Covid-19